Chimeric antigen receptor–engineered T cells for liver cancers, progress and obstacles - Keyu Li; Yaliang Lan; Jiabei Wang; Lianxin Liu (Tumor Biology, 2017)
Chimeric antigen receptor–engineered T cells therapy has become the hottest topic of immunotherapy, as its great successes achieved in treating refractory hematological malignancies. These successes also paved the road to novel strategies of treating various solid tumors including liver cancer. Many specific proteins can be expressed aberrantly in liver cancers; therefore, a series of experimental and clinical researches exploring chimeric antigen receptor–engineered T cells and liver cancer are in progress, acquiring obvious antitumor effect and revealing its feasibility in treating liver cancer. However, lots of challenges and obstacles are emerging simultaneously, such as low infiltration, side effects, safety of chimeric antigen receptor–engineered T cells, and limited data of studies or clinical trials. Researchers have been working out many innovative ways to directly stroke these obstacles, theoretically or practically. This review focuses more on the progress and obstacles from chimeric antigen receptor–engineered T cells therapy to treat liver cancer, summarizing new breakthroughs in shooting those obstacles, meanwhile, hoping to provide enlightenment to this promising immunotherapeutic method.